Marketing Analysis of Kopi Kenangan: Enhancing Customer Purchase Decisions - Sarjono, Haryadi; Gading, Indira Ausani; Fatima, Nazwa; Randy, Aisyah Rahma; Jasmine, Syakira Fakhriya; Putri , Kalea Okta; Soeratin, Boyke Setiawan (Majalah Ilmiah Bijak, 2025)
This research examines the marketing strategy of Kopi Kenangan, a Grab-and-Go coffee brand founded in 2017. On its first day, it sold 700 cups of coffee, showing strong market interest. The company uses the 4P marketing mix (Product, Price, Place, Promotion) effectively, supported by product innovation and active social media promotion. Kopi Kenangan targets Millennials and Gen Z, who often visit coffee shops to relax and socialize. The brand offers a unique customer experience through tasty, affordable drinks, modern café designs, and free WiFi. This research uses a qualitative narrative method, based on secondary data from journals, articles, and market reports. The analysis includes content analysis and SWOT analysis. The results show that Kopi Kenangan has strong brand recognition and market opportunities, but also faces competition and potential risks. Its success lies in building a positive brand image, maintaining high product quality, and using smart marketing strategies. While image attracts interest, product quality is a key factor in actual purchasing decisions. To sustain growth, Kopi Kenangan must continue to innovate, maintain quality, and stay connected with the preferences of young consumers. This study gives valuable insights for businesses aiming to thrive in the competitive coffee market by appealing to the younger generation